New Insights Into the Anatomy, Connectivity and Clinical Implications of the Middle Longitudinal Fasciculus - Latini, Francesco; Trevisi, Gianluca; Fahlström, Markus; Jemstedt, Malin; Alberius Munkhammar, Åsa; Zetterling, Maria; Hesselager, Göran; Ryttlefors, Mats (Frontiers in Neuroanatomy, 2021)
The middle longitudinal fascicle (MdLF) is a long, associative white matter tract connecting the superior temporal gyrus (STG) with the parietal and occipital lobe. Previous studies show different cortical terminations, and a possible segmentation pattern of the tract. In this study, we performed a post-mortem white matter dissection of 12 human hemispheres and an in vivo deterministic fiber tracking of 24 subjects acquired from the Human Connectome Project to establish whether a constant organization of fibers exists among the MdLF subcomponents and to acquire anatomical information on each subcomponent. Moreover, two clinical cases of brain tumors impinged on MdLF territories are reported to further discuss the anatomical results in light of previously published data on the functional involvement of this bundle. The main finding is that the MdLF is consistently organized into two layers: an antero-ventral segment (aMdLF) connecting the anterior STG (including temporal pole and planum polare) and the extrastriate lateral occipital cortex, and a posterior-dorsal segment (pMdLF) connecting the posterior STG, anterior transverse temporal gyrus and planum temporale with the superior parietal lobule and lateral occipital cortex. The anatomical connectivity pattern and quantitative differences between the MdLF subcomponents along with the clinical cases reported in this paper support the role of MdLF in high-order functions related to acoustic information. We suggest that pMdLF may contribute to the learning process associated with verbal-auditory stimuli, especially on left side, while aMdLF may play a role in processing/retrieving auditory information already consolidated within the temporal lobe.